2022
DOI: 10.2337/dc21-2563
|View full text |Cite
|
Sign up to set email alerts
|

Historic Residential Redlining and Present-day Diabetes Mortality and Years of Life Lost: The Persistence of Structural Racism

Abstract: OBJECTIVE The association between structural racism, as captured by historic residential redlining practices under the Home Owners’ Loan Corporation (HOLC), and present-day diabetes mortality, and years of life lost (YLL), remains unknown. RESEARCH DESIGN AND METHODS Age-standardized mortality and YLL data were combined with historic HOLC redlining data for the city of Seattle, WA (a sample of 109 census tract–level observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Table 2 summarizes results by study design and outcome. Across the 13 studies, 7 were cross-sectional (37)(38)(39)(40)(41)(42)(43), 3 were longitudinal (20,44,45), 2 were qualitative (46,47), and 1 was an RCT (48). Sample sizes ranged from 28 to 182,756.…”
Section: Study Characteristics and Outcomes Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 summarizes results by study design and outcome. Across the 13 studies, 7 were cross-sectional (37)(38)(39)(40)(41)(42)(43), 3 were longitudinal (20,44,45), 2 were qualitative (46,47), and 1 was an RCT (48). Sample sizes ranged from 28 to 182,756.…”
Section: Study Characteristics and Outcomes Of Studiesmentioning
confidence: 99%
“…Structural racism differs from structural inequalities in that it reinforces discriminatory beliefs, values, and distribution of resources on the basis of race and ethnicity (19). Structural racism is antecedent to SDOH and serves as an upstream driver of racial and ethnic disparities in health outcomes in the U.S. (20)(21)(22)(23)(24)(25). Other forms of racism in the U.S. that operate as structural mechanisms of inequalities include systemic racism, or racism that is embedded across all societal systems, and institutional racism, or racism that operates at core institutional levels (19,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recent work has further indicated that residents of historically redlined areas are subject to increased rates of gunshot-related ED visits and injuries, increased odds of preterm birth, and higher rates of diabetes specific mortality and years of life lost (YLL). [8][9][10][11][12][13] Linde et al documented the persistence of these associations, noting that HOLC redlining scores consistently explain 45-56% of the variation in census tract-level diabetes mortality rate and 51-60% of the variation in the census tract diabetes YLL rate between the years of 1990 and 2014 in Seattle, Washington. 13 Finally, historically redlined neighborhoods were shown to be subject to worse COVID-19 outcomes than residents within non-redlined areas.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Linde et al documented the persistence of these associations, noting that HOLC redlining scores consistently explain 45-56% of the variation in census tract-level diabetes mortality rate and 51-60% of the variation in the census tract diabetes YLL rate between the years of 1990 and 2014 in Seattle, Washington. 13 Finally, historically redlined neighborhoods were shown to be subject to worse COVID-19 outcomes than residents within non-redlined areas. 14,15 While the mechanisms between historical redlining and health outcomes have not been well examined, evidence suggests that historic redlining operates upstream to suppress social advancement by limiting potential to achieve higher income.…”
mentioning
confidence: 99%